Sustainable development- strategic goal of the knowledge based economy - Madalina Tocan; Stefan Duduman (European Regional Science Association (ERSA), 2010)
Knowledge based economy represents a new phase in the civilizations' development, which promise a new and better way of living. This economy it is based on information and knowledge from all the fields of the economic activities and human existence and has an important economic and social impact. The achieving of a new and better way of living it can be realized thru the sustainable economic development. That is why, starting with the 1980's there have been preoccupations at European Union level regarding policy elaboration towards a sustainable development. Thus, the sustainable development (economic, social, environmental and institutional) becomes a new strategic objective of the knowledge based economy and this new objective can be formulated as "the accomplishment of a dynamic and competitive economy, capable of sustainable economic growth, with more and better jobs and with a grater social cohesion". The present paper it is belt on the following idea: one of the strategic goals of the European Union is to become the most competitive knowledge based economy and sustainable development is one of the key factors of the knowledge based economy
Keywords: 330